2019
DOI: 10.1002/jlb.1hi0219-073rr
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: A flexible kink in the transmembrane domain impairs β2 integrin extension and cell arrest from rolling

Abstract: β2 integrins are the main adhesion molecules in neutrophils and other leukocytes and are rapidly activated by inside-out signaling, which results in conformational changes that are transmitted through the transmembrane domain (TMD). Here, we investigated the biologic effect of introducing a proline mutation in the β2 integrin TMD to create a flexible kink that uncouples the topology of the inner half of the TMD from the outer half and impairs integrin activation. The β2 integrin alpha chains, αL, αM, αX, and α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Although recent technology can identify proteins associating with integrins ( 91 ), the heterogeneity among the different β integrin subunits as well as their diverse function in different cell types averts a general statement about integrin signaling and function. Although the proteins that can directly associate with β 2 integrins or regulate their affinity and function have been reviewed ( 92 ), their contribution to downstream signaling of β 2 integrins in the context of neutrophils is limited ( 38 , 93 97 ). Examples of proteins interacting directly with the cytoplasmic tail of the β 2 subunit and having a known function in neutrophils include Cytohesin-1 ( 98 , 99 ), SYK ( 100 , 101 ), and Filamin A ( 97 ) as we will also discuss below.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent technology can identify proteins associating with integrins ( 91 ), the heterogeneity among the different β integrin subunits as well as their diverse function in different cell types averts a general statement about integrin signaling and function. Although the proteins that can directly associate with β 2 integrins or regulate their affinity and function have been reviewed ( 92 ), their contribution to downstream signaling of β 2 integrins in the context of neutrophils is limited ( 38 , 93 97 ). Examples of proteins interacting directly with the cytoplasmic tail of the β 2 subunit and having a known function in neutrophils include Cytohesin-1 ( 98 , 99 ), SYK ( 100 , 101 ), and Filamin A ( 97 ) as we will also discuss below.…”
Section: Introductionmentioning
confidence: 99%
“…If the β2 TMD is mutated (β2 L697P, right), talin-1 will still bind the intracellular domain and align the beginning of the TMD to an angle >25°, but the kink prevents this from being transmitted to the extracellular domain. The integrin stays bent, but the headpiece opens ( 60 ). Talin head domain (THD).…”
Section: Integrin Activation By Inside-out Signalingmentioning
confidence: 99%
“…This alters the membrane-crossing angle of β TMD, thereby disrupting the outer membrane association of α and β TMDs, which is important for αIIbβ3 integrin activation ( 77 ). Studies showed that these transmitting conformation changes across the cell membrane are also important for both β7 ( 78 ) and β2 integrins ( 60 ). Blocking TMD topology transmission by introducing a TMD kink (L697P mutation) impairs chemokine-induced cell adhesion and β2 integrin extension, but not chemokine-induced β2 integrin high‐affinity confirmation and manganese-induced cell spreading ( 60 ).…”
Section: Integrin Activation By Inside-out Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly of the microfluidic devices used in this study and the coating of coverslips with recombinant human P-selectin-Fc and ICAM-1-Fc has been described previously ( Fan et al., 2016 , Sundd et al., 2012 , Sundd et al., 2011 , Sundd et al., 2010 , Sun et al., 2020 ). Briefly, cleaned coverslips were coated with P-selectin-Fc (2 μg ml-1) and ICAM-1-Fc (10 μg ml-1) for 2 hours and then blocked for 1 hour with casein (1%) at 22-24°C.…”
Section: Materials and Equipmentmentioning
confidence: 99%